The public interest defence and damages for defamation : comparative theoretical and constitutional perspectives for Irish law - Fennell, Sarah (Trinity College (Dublin, Ireland). School of Law, 2009)
The thesis examines the Irish constitutional relationship between the Article 40.6. 1°(i) right to freedom of expression and Article 40.3.2° right to good name in the context of defamation law. It is argued that defamation law is required to serve the values of the Constitution, yet, to date, does not adequately reflect the values underlying speech and reputation rights. This necessitates constitutional re-balancing in defamation law to more appropriately reflect these values. This re-balancing exercise is considered in two areas of defamation law; the public interest defence and damages awards. The conflict between the competing rights of expression and good name must to some extent remain unresolved in individual cases. However, the establishment of a theoretical constitutional framework based on the underlying values of each of the rights should assist in more principled resolution of conflicts. Comparative jurisprudence within the thesis demonstrates the potential for constitutional guarantees in shaping the relationship between speech and reputation rights in defamation law. Despite similar democratic ideals underlying systems of representative government, jurisdictions approach the tensions between freedom of speech and reputation differently. The resolution of rights clashes in other systems of democratic governance can prove both informative and instructive for Ireland. Developments in the foreign jurisdictions selected for discussion in the thesis have tended towards increased protection of public interest speech. This carries implications for the traditional values associated with reputation.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin